FROM LOCAL TO GLOBAL: SURABAYA’S PARADIPLOMACY STRATEGY IN REALISING A CHILD-FRIENDLY CITY - Hastira, Muhammad Fajhriyadi; Maksum, Ali; Hastira, Muh Fichriyadi; Manitra, Ramalina Ranaivo Mikea (Global: Jurnal Politik Internasional, 2026)
Along with the development of decentralisation and subnational diplomacy, strengthening child protection at the city level has become an important part of the global agenda. This research aims to analyse the implementation of the Child-Friendly Cities Initiative in Surabaya City from a paradiplomacy perspective. In addition, this study seeks to explain the synergy between local, national, and global policies and identify opportunities and challenges using literature studies and analysis of official documents from the Ministry of Women's Empowerment and Child Protection (PPPA) and the Surabaya Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (P3APPKB), the Surabaya City Children's Forum, the Surabaya Child-Friendly City Task Force, and UNICEF Indonesia. The research findings show that Surabaya has implemented strategic measures, including preparing an Annual Work Plan, strengthening children’ s participation in decision-making, and developing child-friendly infrastructure. The paradiplomacy strategy has been proven to increase access to international resources and best practices while improving Surabaya’s local governance capacity and global standing. However, challenges such as low public awareness, budget constraints, and suboptimal cross-sector coordination remain. Using data processing based on thematic analysis, this study fills the gap in research on the application of a paradiplomacy perspective in child protection issues, particularly in the implementation of the Child-Friendly Cities Initiative in the Indonesian context.